Vaginal biomarkers that predict cervical length and dominant bacteria in the vaginal microbiomes of pregnant women - Witkin, Steven S.; Moron, Antonio F.; Ridenhour, Benjamin J.; Minis, Evelyn; Hatanaka, Alan; Sarmento, Stephanno G. P.; Franca, Marcelo S.; Carvalho, Francisco H. C.; Hamamoto, Tatiana K.; Mattar, Rosiane; Sabino, Ester; Linhares, Iara M.; et al. (American Society for Microbiology, 2019)
In many impoverished regions of the world, it may not be possible to assess two major risk factors for preterm birth: a short cervical length and the depletion of vaginal lactobacilli. We determined whether measuring specific compounds in vaginal fluid might be a simple, noninvasive, and cost-effective way to predict the bacteria that dominate the vaginal microbiome and indicate the presence of a shortened cervix (<25 mm). Vaginal fluid samples were prospectively collected from midtrimester pregnant women, and the concentrations of D- and L-lactic acid, tissue inhibitor of matrix metalloproteinases TIMP-1 and TIMP-2, matrix metalloproteinases MMP-2 and MMP-8, the 70-kDa heat shock protein, a2 isoform of vacuolar ATPase, and sequestrome-1 were quantified by an enzyme-linked immunosorbent assay (ELISA). The compositions of vaginal microbiomes were assessed by analysis of the V1-V3 regions of 16S rRNA genes, while cervical length was determined by transvaginal ultrasonography. The vaginal microbiomes could be clustered into five community state types (CSTs), four of which were dominated by a single Lactobacillus species. The dominance of Lactobacillus crispatus or Lactobacillus jensenii in the vaginal microbiome predicted the level of D-lactic acid present. Several of the biomarkers, especially TIMP-1, in combination with the subject’s age and race, were significantly associated with cervical length. Using piecewise structural equation modeling, we established a causal network that links CST to cervical length via biomarkers. We concluded that measuring levels of TIMP-1 and D-lactic acid in vaginal secretions might be a straightforward way to assess the risk for preterm birth due to a short cervix and microbiome composition. IMPORTANCE Premature birth and its complications are the largest contributors to infant death in the United States and globally. A short cervical length and the depletion of Lactobacillus species are known risk factors for preterm birth. However, in many resource-poor areas of the world, the technology to test for their occurrence is unavailable, and pregnant women with these risk factors are neither identified nor treated. In this study, we used path analysis to gain an unprecedented understanding of interactions between vaginal microbiome composition, the concentrations of various compounds in vaginal secretions, and cervical length. We identified low-cost point-of-care measures that might be used to identify pregnant women at risk for preterm birth. The use of these measures coupled with appropriate preventative or treatment strategies could reduce the incidence of preterm births in poor areas of the world that lack access to more sophisticated diagnostic methods.
Keywords: Cervical length; Cervix; D-lactic acid; Lactic acid; Lactobacillus; Microbial communities; Preterm birth; TIMP-1; Vaginal microbiome